Land Suitability for Sarimukti Area Surrounding Neighborhood Development Direction - Nandian Mareta; Andre Al Kautsar (Natural B, Journal of Health and Environmental Sciences, 2015)
Sarimukti and surrounding administratively located in the District Rajamandala, Bandung regency, West Java Province. This exciting area of research due to be made the object of a Final Disposal (TPA) which accommodates large-scale garbage from the city of Bandung. Rapid population growth, especially in the area and surrounding Sarimukti requires the development of appropriate settlement in the region. Land suitability analysis was conducted to determine the distribution of the region for the development of settlements. The method is performed in the form of an inventory of primary data include geological data and morphology. After it is weighted by considering the most influential factor. Assessment is done on each cell-cell on the topographical map as a base map. Each cell was given a score and cumulative score is the total score for each cell. Furthermore, by using a statistical method known range of the score most likely to be developed as residential areas. The results are three criteria in the region of the study area is the realm of possibility, region and area constraints limitations.